Rhodamine-immobilized optical hydrogels with shape deformation and Hg(2+)-sensitive fluorescence behaviors - Qu, Zixiang (Sci Rep, 2020)
A highly effective method for the research and development of a novel macroscopic hydrogel sensor and bilayer hydrogel is reported. Based on Rhodamine 6G, an Hg(2+) sensitive fluorescent functional monomer was synthesized, then the monomer was utilized to synthesize hydrogel sensors and bilayer hydrogels. Hydrogel sensor has prominent selectivity to Hg(2+), the bilayer hydrogel has shape changing function additionally. By combining a thermoresponsive hydrogel layer, poly N-isopropylacrylamide (PNIPAM), with an Hg(2+) selective hydrogel layer via macroscopic supramolecular assembly, a bilayer hydrogel is obtained that can be tailored and reswells. The bilayer hydrogel sensor can show complex shape deformation caused by the PNIPAM layer and the Hg(2+)-responsive characteristic of hydrogel sensor layer can be observed under visible light or UV light. This work will provide novel insights for the design and synthesis of novel smart materials with synergistic functions.